Application of the AHP Method for KIP Recommendation Applications -College Students - Satria, Eri; Ilham, Dirja Nur; Budiansyah, Arie; Candra, Rudi Arif; Papuangan, Miswar (Information Technology and Science (ITScience), 2021)
The Smart Indonesia Card (KIP) is an assistance in the form of cash from the government given to students whose parents are less able to finance their education, as a continuation and expansion of the targets of the Poor Student Assistance (BSM) program. KIP has a goal, namely to increase access for children aged 6 (six) to 21 (twenty-one years) to obtain educational services until they graduate from high school to support the implementation of Universal Secondary Education / Pilot Compulsory Education 12 (twelve) years, prevent students from the possibility of dropping out of school or not continuing their education due to economic difficulties. The KIP-Kuliah, formerly known as Bidikmisi, is presently in service. They may find it difficult to determine who is a qualified candidate to become a recommendation for KIP-Kuliah recipients who will be presented to the system since many variables and assessments will be passed in determining the prospective KIP-Kuliah recipients. Therefore, from this problem, a system is needed that can quickly and accurately assess the eligibility of KIP-Lecture recipients without having to sort out the files that have been collected one by one. As a result, it is deemed necessary to develop a decision-making system to address the existing issues. The steps of research that will be carried out to create a decision support system will collect criteria and sub-criteria from the assessment and then enter them into the calculation formula or method employed, namely the AHP method.